Invasive Amazon sailfin catfish in Bangladesh: wild distribution, environmental and perceived socio-economic consequences - Md Shakhawate Hossain; Surya Gentha Akmal; Miloš Buřič; Jiří Patoka (Aquatic Invasions)
Amazon sailfin catfish are native to Latin Arica (Siluriformes: Loricariidae: Pterygoplichthys) and are popular around the world as ornamental fish. It is well-documented that these species are highly successful invaders and very prone to forming new geographical ranges. However, once established, eradicating a new population is a very challenging task. In Bangladesh, species of the genus Pterygoplichthys are expected to spread widely and have a severe detrimental impact on ecosystem health, biodiversity and economics. Here we provide new information on the future probable establishment of non-native populations of these species in the wild using a climate-matching analysis and highlight their potential area of occurrence. The potential socio-economic consequences are also discussed, as are the public perception of these species and probable economic damages caused. Control of the import of similar species, their culture and intentional or unintentional release into open water is urgently required.